2014
DOI: 10.1002/cbic.201402585
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Inhibitor‐Free HIV‐1 Protease Derived from NMR Spectroscopy in a Weakly Oriented Solution

Abstract: Flexibility of the glycine-rich flaps is known to be essential for catalytic activity of the HIV-1 protease, but their exact conformations at the different stages of the enzymatic pathway remain subject to much debate. While hundreds of crystal structures of protease-inhibitor complexes have been solved, only about a dozen inhibitor-free protease structures have been reported. These apo-structures reveal a large diversity of flap conformations, ranging from closed, to semi-open and wide-open. To evaluate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 64 publications
(38 reference statements)
3
43
0
Order By: Relevance
“…The flaps of free protease are predominantly closed (23), blocking access to substrate; flap opening is a rare process resulting in slow productive complex formation (lifetime ∼100 ms) (22), which is manifested by a significant reduction in 1 H N / 15 N cross-peak intensity for residues at the SP1jNC junction of ΔGag…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The flaps of free protease are predominantly closed (23), blocking access to substrate; flap opening is a rare process resulting in slow productive complex formation (lifetime ∼100 ms) (22), which is manifested by a significant reduction in 1 H N / 15 N cross-peak intensity for residues at the SP1jNC junction of ΔGag…”
Section: Resultsmentioning
confidence: 99%
“…These ultra-weak complexes, involving quite extensive interactions surfaces, are initially formed and serve to guide the formation of productive complexes, thereby dictating the sequential order of Gag cleavage (i.e., we speculate that these transient encounter complexes accelerate the formation of productive complexes). The formation of productive complexes at the Gag cleavage sites are associated with rare conformational transitions involving flap opening (22,23) that are detected by changes in cross-peak intensities and chemical shifts (intermediate exchange; see Fig. S8).…”
Section: Methodsmentioning
confidence: 99%
“…There are multiple ways of using RDCs to study the dynamics of proteins. They are well-suited for comparing the structural state of a protein in solution to structures obtained from x-ray crystallography (Bernado & Blackledge, 2004;Bouvignies et al 2005Bouvignies et al , 2006Clore & Schwieters, 2004b;Salvatella et al 2008), as shown elegantly for various states of the HIV-1 protease (Roche et al 2015) and arginine kinase (Niu et al 2011). As an extension of this approach, it is also possible to determine the distribution of structural states in proteins by using ensemble methods (Esteban-Martin et al 2010, 2014; Fenwick et al…”
Section: Residual Dipolar Couplingsmentioning
confidence: 99%
“…Crystallographic analysis of several highly resistant mutants share perturbations in the active site, flap regions, 80’s loop, or inter-subunit interactions, which are likely to be mechanisms inducing loss of susceptibility to PIs. In addition, the highly resistant variants are proposed to have increased occupancy of open conformational states relative to wild type enzyme, as assessed by Electron Spin Resonance [48] and Nuclear Magnetic Resonance [49]. These structural and functional insights into HIV PR drug resistant mutants are invaluable in developing novel therapeutics for future AIDS treatment.…”
Section: High Level Resistance From Multiple Resistance Mutationsmentioning
confidence: 99%